Dinâmica sazonal da contaminação microbiana da água do Parque Ecológico do Tietê - (:unkn) unknown (Universidade Brasil, 2021)
The quality of water resources can be altered by human activities carried out in watersheds. These changes can lead to the occurrence of antibiotic-resistant bacteria and compromise public health. The aim of the present study was to evaluate the presence and concentration of total coliforms and Escherichia coli in the water at the Parque Ecológico do Tietê (Ecological Park Tietê) in São Paulo, the antibiotics resistance of isolated E. coli and the correlation between physical-chemical environmental and microbiological variables of the water. Sample localities were georeferenced and identified as P1 - Drinking water from the distribution system; P2 - Main lagoon of the park; and P3- Connection between the main lagoon and the Tietê River. Physical-chemical and microbiological variables were measured, thus Principal Component Analysis (PCA) and linear regression models were performed to verify the correlation between these variables. The microbiological analysis was performed by inoculating the samples in 3MTMPetrifilmTM plates, incubated at 37 ° C for 48 hours and the E. coli isolated had their antibiotic resistance profile tested by the disk diffusion technique using Mueller Hinton agar. Total coliforms and E. coli were not identified at P1. Total coliforms were identified in 64% of the samples and E. coli was identified in 36% of the samples. Water temperature and precipitation were the most significant correlated variables and the linear regression models showed the influence of seasonality on the concentration of E. coli in the water, with the highest values in the rainy and warmer seasons. The isolated E. coli showed greater resistance to erythromycin (82%) and amoxicillin (55%) in P2, and to erythromycin (82%) and amoxicillin (27%) in P3, with the presence of multiresistant isolates at both points. No strain showed resistance to amikacin. The high rate of resistance of E. coli to the antibiotics frequently used in human and veterinary medicine demonstrates that the contribution of these substances in aquatic ecosystems over the years has exerted a selection pressure on microorganisms, assisting the appearance and spread of resistant bacteria, changing the environmental biota and turning these locations in possible reservoirs of antibiotic resistance.
Keywords: Bactérias; Coliformes; Escherichia coli; Recursos Hídricos; CB